Functional analysis of polyketide synthase genes in the biocontrol fungus Clonostachys rosea. Issue 1 (December 2018) - Fatema, Umma; Broberg, Anders; Jensen, Dan; Karlsson, Magnus; Dubey, Mukesh
Abstract Clonostachys rosea is a mycoparasitic fungus used for biological control of plant diseases. Its genome contains 31 genes putatively encoding for polyketide synthases (PKSs), 75% of which are arranged in biosynthetic gene clusters. Gene expression analysis duringC .rosea interactions with the fungal plant pathogensBotrytis cinerea andFusarium graminearum showed common and species-specific induction of PKS genes. Our data showed a culture media dependent correlation between PKS gene expression and degree of antagonism inC .rosea . Thepks22 andpks29 genes were highly induced during fungal-fungal interactions but not during pigmentation, and gene deletion studies revealed that PKS29 was required for full antagonism againstB .cinerea, and for biocontrol of fusarium foot rot on barley. Metabolite analysis revealed that Δpks29 strains has a 50% reduced production (P = 0.001) of an unknown polyketide with molecular formula C15 H28 O3, while Δpks22 strains lost the ability to produce four previously unknown polyketides named Clonorosein A-D. Clonorosein A and B were purified, their structures determined, and showed strong antifungal activity againstB .cinerea andF .graminearum . These results show that PKS22 is required for production of antifungal polyketide Clonorosein A-D, and demonstrate the role of PKS29 in antagonism and biocontrol of fungal plant diseases.